Clinical profiles and care of transgender children and adolescents who receive specialized consultations: do individuals who are assigned female at birth differ? - Chystelle Lagrange; Nina Verger; Julie Brunelle; Fanny Poirier; Hugues Pellerin; Nicolas Mendes; Gregor Mamou; Nifoular Forno; Laetitia Martinerie; David Cohen; Agnès Condat (Child and Adolescent Psychiatry and Mental Health)
Abstract Context Clinical data on transgender children and adolescents are scarce, and sample sizes often do not allow for comparisons according to sex assigned at birth. Besides, most gender identity clinics have pointed to a recent switch in favor of an increase in the number of adolescents assigned females at birth (AFAB) over assigned males at birth (AMAB). Method We collected data on sociodemographic characteristics, and psychiatric and social vulnerabilities according to sex assigned at birth for all youths who were treated at the French largest gender identity clinic. In addition, management modalities for gender transition were discussed in multidisciplinary concertation meetings. Results We collected data from 239 youths [162(68%) AFAB, 74(32%) AMAB, and 3(1%) intersex; mean age = 14.5(± 3.16) years]. The distribution of age at referral was better explained by two clusters (C1: N = 61, mean age = 11.3 years, with more AMAB; C2: N = 175, mean age = 15.9 years with more AFAB). 215(91%) youths had gender incongruence, with 32% reporting it before puberty. School drop-out, suicidality, depression, and anxiety were common and occurred significantly more often in the AFAB group. 178(74%) youths experienced social transition within the family, and 144(61%) at school [mean age = 15.13(± 2.06) years]. The social transition was more frequent in the AFAB group. Twenty-six (11%) youths received puberty blockers [mean age = 13.87(± 2.31) years], and 105(44%) received gender-affirming hormones [mean age = 16.87(± 1.4) years]. AMABs were more likely to take puberty blockers, and there was no difference in the proportion of AMAB and AFAB taking gender-affirming hormones. Surgical requests (mainly torsoplasty) were very rare. Conclusion Age at referral should be considered when exploring gender incongruence. During adolescence, we found that gender incongruence has substantial social and psychological effects, particularly on AFAB youths, possibly explaining their higher referral rates to specialized centers, as in other specialized clinics around the world.